Educated Unemployment in the Digital Age: Between Overqualification and Skills Mismatch in the Modern Job Market - Rieke Oktaviyanti; Maya Panorama (CURRENT ADVANCED RESEARCH ON SHARIA FINANCE AND ECONOMIC WORLDWIDE, 2025)
The development of the digital economy creates new job opportunities, but also increases educated unemployment due to the mismatch between graduate competencies and the needs of the workforce. The phenomena of overqualification and skill mismatch are major obstacles to labor absorption. This study aims to analyze the factors causing educated unemployment in the digital era and the relationship between overqualification and skill mismatch. The method used is a descriptive qualitative approach through literature studies from scientific journals, employment reports, and secondary data. The results show that approximately 35% of young workers in Indonesia experience a mismatch between education and work, with 22.36% classified as overeducated. Furthermore, the level of overqualification in certain groups can reach 50%, while skill mismatch is the dominant phenomenon. The main causes include rapid digital transformation, curriculum misalignment with industry needs, and low adaptive skills. Therefore, synergy is needed between universities, industry, and the government to make education more relevant to the job market.